Inculcating ethics through action learning - Hasan, Hazmilah; Bakar, Norasiken; Shahbodin, Faaizah; Hussain, Kalthom (2011)
Action learning has been one of the strategy in delivering teaching and learning amongst students. Educators and scholars exploring and investigating on ways or methodologies that can ensure teaching and learning activity in class are fun and benefited students as to knowledge, generic skills/soft skills transferred and practices. This study explored ethics transferred amongst students through action learning in mind mapping activity. Researcher found that good values such as integrity and objectivity could be transferred through action learning.